Toward a better understanding of coaches` information search in talent selection: A first experimental investigation on the basis of the iCodes model - Lath, F.; Koopmann, T.; Schorer, J. (Sport, Exercise, and Performance Psychology, 2025)
The iCodes model by Jekel et al. (2018) states predictions about the information search in decision-making processes. Previous research validated the attraction search effect in various nonsport scenarios. This investigation explores coaches` decision making in athlete selection contexts using the iCodes model`s main hypotheses. Hypothesis 1 states that the probability of coaches searching for a particular criterion regarding an athlete increases with the criterion`s validity. Hypothesis 2 states that when information is available, information search will be directed toward the more attractive athlete as an option (i.e., the attraction search effect). Moreover, a third hypothesis is added: The information search process differs between coaches from different sports. Seventy-five coaches were confronted with 52 option-information boards. In each trial, coaches opened athletes` criteria and selected one athlete as "most talented." After completing all trials, coaches ranked the criteria regarding their validity for athlete selection. Results showed evidence in favor of Hypotheses 1 and 3 but indeterminate regarding Hypothesis 2. Overall, this study presents an extension of the iCodes model and contributes to a better understanding of the underlying mechanisms of the coach`s eye. (PsycInfo Database Record (c) 2025 APA, all rights reserved)